Radioresistance and brain metastases: a review of the literature and applied perspective - Youssef, Andrew; Sahgal, Arjun; Das, Sunit (Frontiers in Oncology, 2024)
Intracranial metastatic disease is a serious complication of cancer, treated through surgery, radiation, and targeted therapies. The central role of radiation therapy makes understanding the radioresistance of metastases a priori a key interest for prognostication and therapeutic development. Although historically defined clinic-radiographically according to tumour response, developments in new techniques for delivering radiation treatment and understanding of radioprotective mechanisms led to a need to revisit the definition of radioresistance in the modern era. Factors influencing radioresistance include tumour-related factors (hypoxia, cancer stem cells, tumour kinetics, tumour microenvironment, metabolic alterations, tumour heterogeneity DNA damage repair, non-coding RNA, exosomes, methylomes, and autophagy), host-related factors (volume effect & dose-limiting non-cancerous tissue, pathophysiology, and exosomes), technical factors, and probabilistic factors (cell cycle and random gravity of DNA damage). Influences on radioresistance are introduced and discussed in the context of brain metastases.